Self-Management Technical Modules As Personal Guidance and Counseling Media For High School Students - Tuti Wantu; Maryam Rahim; Arwildayanto; Idriani Idris; Nurul Maulida Alwi; Mohamad Awal Lakadjo; Melsin Dunggio (Jurnal Pedagogi dan Pembelajaran, 2023)
The current phenomenon shows that there are still many students who still need to gain a higher level of self-management. It shows the importance of improving high school students' self-management. This research aims to produce a self-management technique module that is suitable for use as a medium for personal guidance and counseling for high school students. This research uses the Research and development (R&D) method with the following stages: potential and problems, data collection, product design, design validation, design revision, product testing, and product revision. The expert test subjects consisted of media guidance and counseling experts, personal guidance and counseling experts, and Indonesian language experts. This research involved a small group consisting of four Guidance and Counseling teachers as experimental subjects. Questionnaires were used for data collection. Data from expert validation and small group testing were analyzed qualitatively. The results of expert validation and product testing concluded that "the self-management techniques module is suitable for use by high school students as a personal guidance and counseling tool." Thus, this self-management module can be recommended for application as a medium for personal guidance and counseling for high school students.